Using the ACTFL OPIc to assess proficiency and monitor progress in a tertiary foreign languages program. (July 2019) - Isbell, Daniel R.; Winke, Paula; Gass, Susan M.
Language tests are useful for many purposes, including monitoring language learning progress and evaluating language programs. This study investigated the interpretations and usefulness of the American Council on the Teaching of Foreign Languages (ACTFL) Oral Proficiency Interview – Computer (OPIc) scores across four languages at a large US public university, focusing on (1) the influence of learner backgrounds on oral proficiency variation and growth and (2) patterns in growth across languages. Two years of OPIc score data from 814 students studying Chinese ( n = 143), French ( n = 251), Spanish ( n = 374), and Russian ( n = 46) were collected, together with survey data on language learning experiences and motivation. Each participant had two to four OPIc scores. A growth curve analysis using mixed-effect modeling revealed that language learning experience and motivation explained approximately 43% of variation in initial proficiency and 23% of variation in rates of change over time. The target language had no unique effects on initial proficiency or change over time. On average, learners gained roughly one-third of an ACTFL sublevel per semester of study (while controlling for differences in their backgrounds). Findings are informative for appropriate interpretations and uses of OPIc scores in tertiary educational settings, but also question individual growth-tracking suitability on a semester-by-semester basis.